Hair determination of per- and polyfluoroalkyl substances (PFAS) in the Italian population. (30th June 2021) - Piva, E.; Giorgetti, A.; Ioime, P.; Morini, L.; Freni, F.; Faro, F. Lo; Pirani, F.; Montisci, M.; Fais, P.; Pascali, J.P.
Highlights: The presence of twenty PFAS was investigated by LC-QTOF in the hair of 86 subjects from four Italian regions. 66.4 % of the analyzed population had quantifiable amounts of PFAS. PFOA and PFOS were the chemicals most frequently detected, followed by PFBA, PFNA, PFDA, PFUnA and PFHxS. Geographical-based differences in the presence and prevalence of PFAS in hair were found. No significatively differences in PFAS presence were observed between genders nor across age classes. Abstract: Per- and polyfluoroalkyl substances (PFAS) are anthropogenic chemicals present in the environment and defined as persistent organic pollutants (POPs). The interest in these forms of contaminants is related to the toxic consequences for health derived from exposures and bioaccumulation processes. The present research aims at assessing differences in the exposure of PFAS in the Italian population by hair analyses. To this aim, 20 compounds of the PFAS family were investigated in hair of 86 Italian subjects distributed across the regions of Veneto, Emilia-Romagna, Lombardy and Marche. The applied method was ad hoc developed in a previous research and included SPE extraction and LC-QTOF analysis. In the analyzed population, 66.4 % had quantifiable amounts of one or more PFAS molecules (up to 4 compounds); mean PFAS content, expressed as sum of PFAS, was 0.1457 ng/g, ranging from "not detected" to 0.85 ng/g (SD 0.1867). PFOA and PFOS were the chemicals most frequently detected, with mean concentrations of 0.1402 ng/g and 0.1155 ng/g, respectively. PFBA was detected in 9.3 % of subjects with a mean concentration of 0.3760 ng/g; PFNA in 3.5 % of subjects with mean concentration 0.12 ng/g; PFDA was found in one subject at the concentration of 0.541 ng/g. PFUnA and PFHxS were detected below the limit of quantification. The overall results displayed differences in the presence and prevalence of PFAS in hair of the Italian population on a geographical base. On the contrary, no significatively differences in the amount of PFAS were observed when considering gender or age classes. On this base, hair can be considered a good diagnostic tool to assess PFAS exposure on a regional-scaled base. Of course, more studies are required to infer PFAS internal dose from hair results due to its peculiar detection window and to interpretative issues derived from external contamination.